The Application of Information and Communication Technology in Malay Language Teaching: Teachersâ Perspectives - Othman, Yahya (ASPENSI in Bandung, Indonesia, 2010)
ABSTRACT: Information and Communication Technology (ICT) in language teaching and learning is among considered suitable with the current education needs. However, the issue is regarding how far do teachers master the concept of computer-aided language learning, their skills in performing teaching by using ICT, mastery level as well as the constructions faced by the teachers. Therefore, this research is intended to examine the issues stated above. The research sample consisted of 87 Malay language teachers who were randomly selected around the Hulu Langat District in Selangor Darul Ehsan, Malaysia. In this survey research, questionnaires were used to collect the relevant data. The research findings show that the computer-aided language teaching concept is being understood in various dimensions. In terms of training, most of the respondents have already attended basic computer courses. However, the courses related to teaching material preparation using multimedia, the usage of internet and website design are given less attention. The use of computer in Malay language teaching is able to increase studentsâ ability to master Malay language better. Therefore, aspects such as in-service training, preparation of interactive learning materials, encouraging the use of internet in teaching as well as preparing suitable technology with current situation are required to be given attention.Key words: Information and Communication Technology (ICT), language teaching and learning, teachersâ perspectives, and Â studentsâ ability.About the Author: Yahya Othman, Ph.D. is a Senior Lecturer at the Sultan Hassanal Bolkiah Institute of Education (SHBIE) University of Brunei Darussalam (UBD), Jalan Tungku Ling BE1410, Bandar Seri Begawan, Negara Brunei Darussalam. He can be reached at: yaoth@yahoo.comHow to cite this article? Othman, Yahya. (2010). âThe Application of Information and Communication Technology in Malay Language Teaching: Teachersâ Perspectivesâ in SOSIOHUMANIKA: Jurnal Pendidikan Sains Sosial dan Kemanusiaan, Vol.3, No.2 [November], pp.209-218. Bandung, Indonesia: Minda Masagi Press, UNIPA Surabaya, and UMS Kota Kinabalu, Malaysia, ISSN 1979-0112. Chronicle of article: Accepted (September 28, 2010); Revised (October 30, 2010); and Published (November 20, 2010). Â Â